Developing a Model of Literary Appreciation Learning in Higher Education - Mulyani Mulyani; Imran Imran (Science and Education Journal (SICEDU), 2026)
This article discusses the development of literary appreciation learning models in higher education, emphasizing systematic, creative, and collaborative approaches. The aim is to identify strategies that enhance students’ interest, comprehension, and engagement in appreciating literary works. The ADDIE model serves as the primary framework, combined with creative-innovative and collaborative methods. Findings suggest that integrating theory, practice, and digital technology into literary appreciation learning significantly improves students’ cognitive, affective, and evaluative abilities.